Financial Markets and Institutions - Frederic S. Mishkin (Pearson Education Limited, 2016)
The global financial crisis, which has been the worst financial crisis the world has experienced since the great depression, has completely changed the nature of financial markets and institutions. Given what has happened, the study of financial markets and institutions has become particularly exciting. There is major new material in every part of the text. The book of financial markets and institutions consist of seven part and twenty seven chapter. The material in part one is introduction includes discuss why study financial markets and institutions, and overview of thr financial system. The second part discuss fundamentals of financial markets includes about interest rates mean and their role in valuation; interest rates change, risk and term structure affect interest rates, and financial markets efficient. The third part of this text about fundamentals of financial institutions includes financial institutions exist and financial crises occur and damaging to the economy. The fourth discuss about central banking and the conduct of monetary policy. The material in part five is financial markets includes the monery markets, the bond market, the stock market, the mortgage markets, the foreign exchange market and the international financial system. The material in part six is the financial institutions industry includes banking and the management of financial institutions, financial regulation, banking industry, the mutual fund, insurance companies and pension funds, and discuss investment bank, security brokers and dealers, and venture capital firms. The material in part seven is the management of financial institutions includes risk management in financial institutions and hedging with financial derivatives. The last material in the book are chapters on the web includes financial crises in emerging market economies, savings associations and credit unions, and finance companies.